KARAKTERISTIK KEPEMIMPINAN PENDIDIKAN ISLAM - Saefudin Zuhri; Adi Saputra; Hani Tria; Dahlan Anwar (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
As we all know that today there are many differences of opinion from political elites, statesmen and even scholars in the country of Indonesia about being like a leader and the character of the prospective leader's personnel who are ideal for the country and understand the ideology of Pancasila. This diverse country with many tribes, cultures and even religions has invited quite a long and ongoing controversy, and it is not uncommon to argue with each other, blaspheme against each other in various ways that are hurled as references in order to defend the arguments of each group, whether by political elites, cultural figures and even religious leaders. Therefore, the author feels it is important to briefly discuss the contents in this journal. how Islam as the majority religion in the equatorial emerald country responds to endless differences of opinion and can result in divisions between the nation's children and even Muslims themselves. Therefore, here the author will describe little by little related observations about Leadership.